Tank Irrigation by Muslim case study ( Hauz Khas ) a Historico – Geographical study (مجلة ديالى للبحوث الانسانية, 2022)
The study end to highlight and dedicate sites of spatial and seasonal pollution of khurasan stream from the sites that we take samples from five sites from the study area . The study best on spatial analysis for difference sites from the canal . The study depend on field study which dedicate the sites of pollution places and sources . We did laboratory test for each source of polletance in the course of the stream.                                                We choose twelve elements from the chemical elements and by two samples for the period  (1-8 – 2009 ) up to (1- 5 -2010 ) . The study nature need research work also , the research content three sections , in the first section we took the theoretical base introduction , problem , hypothesis , the research aim and the study area limit as well as the source of the data and the way we took the samples for analysis . The second section come to spatial analysis for the pollution of the water of stream in the same time we derived the PH of the stream water, also the biological oxygen demand and chemical oxygen demand . In the last section which come to evaluate the usability of Khurasan canal water for different uses .